Effect of Planting Dates on the Performance of Promising Pigeonpea Genotypes under NEHZ - Kithan, Lowrence; Sharma, Malini B.; Longchar, Akumla (International Journal of Economic Plants, 2020)
A field experiment was conducted during Kharif season of 2017 at All India Coordinated Research Project (AICRP) on pigeonpea experimental farm at School of Agricultural Sciences and Rural Development (SASRD), Nagaland University, Medziphema Campus. The objective of the study was to investigate the effect of different dates on performance of some improved pigeonpea varieties. The experiment comprised of three planting dates (1st June, 15th June and 1st July) as factor A and three pigeonpea varieties (UPAS 120, MANAK and PARAS) as factor B. The experiment was laid out in factorial randomized block design (FRBD) with three replications. Among growth parameters, maximum plant height (163.2 cm) and number of branches (15.8) were recorded with variety UPAS 120 at first date of sowing (1st June). Among yield parameters, maximum number of pods per plant (114.9) and maximum grain yield (982.2 Kg ha-1) were recorded at first date of sowing (1st June) and with variety UPAS 120 (113.8 and 968.8 Kg ha-1).